The impact of population growth on housing food security and transportation - Ambar, Nanik; Lestari, Dewi; Lathifah, Lina Nidau (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Rapid population growth and its impact on the environment is a major problem facing the world today, in addition to other issues that also require serious handling and attention. Rapid population growth, especially in cities and urban areas, puts pressure on the fulfillment of population needs that must be provided to ensure the survival of the population. Population growth has an impact on the increasing needs of the population for affordable housing, food needs, transportation. Method: This research uses a qualitative approach based on case studies and literature reviews. This approach involves a critical and in-depth evaluation of previous research, focusing on data collected from various sources related to the impact of population growth on affordable housing, food needs, and sustainable transportation. Findings: The rate of population growth has an impact on environmental sustainability, as a result of the exploitation of natural resources to fulfill various needs, including food needs. Population growth has a linear effect on the demand for food, such as rice and tubers, through the provision of agricultural land. This increase in consumption value occurs in an increasingly limited stock of natural resources, therefore a food fulfillment strategy is needed to achieve national food security and sovereignty, to meet the needs of the population and for food stocks to anticipate undesirable things, such as natural disasters and crop failures. Some of the efforts that can be made are food diversification, intensification, and extensification of agriculture accompanied by the active role of the government in providing infrastructure and supporting policies. Population growth also affects the level of population mobility. Each individual carries out daily activities such as school, work and other activities. This population mobility greatly affects the use of transportation modes to reach certain destinations. The mode of transportation consists of private vehicles and public vehicles. Conclusion: If the use of private vehicles is more than public vehicles, there is the potential for traffic congestion. In addition, the more vehicles used, the greater the carbon emissions produced so that it can cause greenhouse gas effects. One of the efforts that can be made is to implement sustainable transportation management through Transit Oriented Development (TOD) in the provision of transportation modes. TOD is expected to make private vehicle users switch to using public transportation. Novelty/Originality of this study: This research proposes a holistic approach to address the impacts of urban population growth, combining strategies for food diversification, transit-based development, and affordable housing. This framework is expected to be a practical innovation for sustainable urban development in countries with rapid population growth.